Development of descriptive e-big book based on writing workshop model to improve writing skills - Dina Tri Suryani; Panca Dewi Purwati (Jurnal Prima Edukasia, 2026)
Problems in writing instruction can be caused by the use of learning media or models that are not sufficiently relevant. Digital learning media such as the E-Big Book are considered to have the potential to increase student engagement because they combine text, images, and interactive activities. This study aims to develop the Descriptive E-Big Book media based on the Writing Workshop model, test the media’s validity, and assess its effectiveness in improving the simple sentence writing skills of second grade students at Imama Islamic Elementary School. This study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the Descriptive E-Big Book media, created using the Canva Pro application, received a content validity score of 96.875%, a linguistic validity score of 96.875%, and a media validity score of 93.75%. The average score of the 26 students was 88.11, which meeting the minimum passing score of 70. This indicates that the development and implementation of the Descriptive E-Big Book learning media based on the Writing Workshop model is effective in improving simple sentence writing skills among second-grade students in elementary school.